Cerâmicas de PZT modificadas com terras raras sintetizadas usando o método dos complexos oxidantes de peróxido (OPM) e sinterizadas por micro-ondas - Yamada, Liliam Kaori (2013)
The Pb(Zr0,52Ti0,48)O3 solid solution in morphotropic phase and its modified (RExPb1-x)(Zr0,52Ti0,48O3) with RE = La, Pr or Nd and x = 0.05, 0.10, 0.15, 0.20, 0.30, 0.38 and 0.45 were satisfctorily prepared by oxidant peroxo method (OPM), in which the solid solutions of Pr- and Nd-PZT were first synthesized by this technique. The PZT medication with RE caused the loss of tetragonal character and decreased stiffness of Zr / TiO6 octahedra with the meeting of ceramic saturation in 10 % to Pr and 20 % to La and Nd. The optimization of calcination condition of PZT powders at 600 °C / 0.5 h caused to be impurity free in its structure. Futhermore, showed grains less coalesced with size more homogeneous with little necks formation in relation to other thermal conditions performed. On the other hand, the RE-PZT powders cacined in the same condition showed impurities in its structure which was not ideal for complete crystallization of the powder. The ceramic bodies, prepared from these powders calcined at 600 °C / 0.5 h with sintering in microwave oven at three different conditions: 900 °C / 2 h, 1000 °C / 0.5 h and 1000 °C / 2 h, showed relative density values over 98 % for pure PZT and below 96 % for RE-PZT without change in value between the different sintering conditions performed.